2008
DOI: 10.1038/sj.ejhg.5202003
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of fasting plasma triglyceride response to fenofibrate treatment

Abstract: Metabolic response to the triglyceride (TG)-lowering drug, fenofibrate, is shaped by interactions between genetic and environmental factors, yet knowledge regarding the genetic determinants of this response is primarily limited to single-gene effects. Since very low-density lipoprotein (VLDL) is the central carrier of fasting TG, identifying factors that affect both total TG and VLDL -TG response to fenofibrate is critical for predicting individual fenofibrate response. As part of the Genetics of Lipid Lowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Fibrates stimulate cellular fatty acid uptake, conversion to acyl-CoA derivatives, and catabolism by the beta-oxidation pathways, which, combined with a reduction in fatty acid and triacylglycerol synthesis, results in a decrease in VLDL production. It has been shown that interindividual variations in the response to fenofibrate could be partially driven by genetic factors (31,32). In this regard, our study shows that the fenofibrate-induced reduction of triacylglycerol concentrations was more evident in subjects within the higher risk group (R) than in those in the intermediate (M) and protective (P) genotype groups.…”
Section: Discussionsupporting
confidence: 50%
“…Fibrates stimulate cellular fatty acid uptake, conversion to acyl-CoA derivatives, and catabolism by the beta-oxidation pathways, which, combined with a reduction in fatty acid and triacylglycerol synthesis, results in a decrease in VLDL production. It has been shown that interindividual variations in the response to fenofibrate could be partially driven by genetic factors (31,32). In this regard, our study shows that the fenofibrate-induced reduction of triacylglycerol concentrations was more evident in subjects within the higher risk group (R) than in those in the intermediate (M) and protective (P) genotype groups.…”
Section: Discussionsupporting
confidence: 50%
“…Smith et al [93], for example, with the GOLDN study data reported 4 SNPs ( APOA4_M35, APOC3_3U386, ABCA1_I27943 , and LIPC_T224T ) responsible for a large portion of the SNP-covariate interaction that predicted the TG change. Different from previous studies, we performed multivariate factor analysis and random coefficients growth curves on the repeated measures.…”
Section: A Case Study: Fenofibrate Treatment In the Goldn Study Anmentioning
confidence: 99%
“…However, known genetic factors only account for a modest proportion of inherited heterogeneity in treatment response (1), highlighting the need for cost-effective identification of novel, especially rare, pharmacogenetic variants. Previous simulations have shown that family-specific linkage analysis provides a powerful way to select samples that carry rare alleles, even when the aggregate evidence of linkage is weak (2).…”
Section: Introductionmentioning
confidence: 99%